Evolution of Menispermaceae - (:unkn) unknown (My University, 1986)
The polarity of character states of pollen, leaf, endocarp, seed, perianth, androecium, and gynoecium within the Menispermaceae is established on the basis of maximum correlation of characters. Instances of parallel evolution are explained. The origin and spread of the different genera, which manifest the various combinations of character states, are analysed in the light of the position of the continents during the Cretaceous and Tertiary periods. Menispermaceae seem to have originated in the lowlands of Africa during the Cretaceous when South America, Africa, Madagascar, and India were close to one another. Consequent to the continental drift each land mass might have carried with it some elements of the primitive Menispermaceae which must have eventually given rise to the neoendemics. The Sino–Japanese spread of this family seems to have been post-Himalayan. "Malesia" appears to be a secondary centre of diversification of taxa derived from India. Cissampelos, Cocculus, and Stephania seem to have originated in India and entered Africa during the Miocene. The Eocene endocarps of North America show affinity with those of the London Clay, which in turn were probably derived from the African stock. Among the extant species of North America only Calycocarpum lyonii seems to be the relic of the North American Tertiary flora and the rest appear to have been derived from east Asia.
Keywords: African Research